Human papillomavirus self-sampling in Asia: a systematic review - Ji, Xuechao; Hao, Menglin; Wang, Yixiao; Kong, Wenzhi; Pan, Zangyu; Sun, Qi; Miao, Jinwei (Frontiers in Microbiology, 2025)
BackgroundHuman papillomavirus (HPV) self-sampling may be an accurate and effective alternative sampling method to conventional cervical cancer screening methods. This systematic review compares the accuracy and acceptance of self-sampling to clinician sampling for HPV testing in Asia.MethodsThe PubMed, Cochrane Library, Cumulative Index to Nursing and Allied Health, and Web of Science databases were searched for publications published from the establishment of the database to 2023. The risk of bias was assessed using the QUADAS-2 tool for studies included in this review. All studies evaluating the accuracy and acceptance of HPV self-sampling, and agreement of self- and clinician-collected samples in Asia were included. The accuracy of each study was demonstrated through the sensitivity and specificity in diagnosing cervical intraepithelial neoplasia or cancer, as well as the detection rate of HPV. The agreement between the two sampling methods was assessed based on the detection outcomes of HPV. Acceptance was indicated by women’s preferences for HPV self-sampling.ResultsSixty-seven studies including 117,279 adult, female participants were included in this review. The type of HPV screening, other intervention components, study design, sample size, follow-up period, analysis method, numerical outcomes, results, and limitations were extracted from each study. The sensitivity and specificity of HPV self-sampling in detecting cervical intraepithelial neoplasia were higher than 80% and 70%, consistent with the results of HPV clinician sampling. The consistency between self-sampling and clinician-sampling was high in most studies, and the kappa value was more than 0.7. Women had high acceptance of self-sampling but expressed some concerns.ConclusionSelf-sampling for HPV testing can significantly improve cervical cancer screening coverage, especially in areas with limited medical resources or reluctance to accept physician sampling. In most studies, the accuracy and acceptance of HPV self-sampling was comparable to clinician sampling. However, the diagnostic criteria and HPV detection methods still need to be adjusted due to the low sensitivity of HPV self-sampling in some studies in China and India. Targeted health education should be carried out to improve the acceptance of HPV self-sampling in women.Systematic review registrationhttps://inplasy.com/?s=INPLASY202520107, INPLASY202520107.